PERSEPSI STAF DOSEN TERHADAP INTERIOR RUANG B.78 DI JURUSAN SENI RUPA FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI PADANG - Syafriyadi Surya Ellyka, Heldi, Syafril R (Universitas Negeri Padang, 2013)
The purpose of this study was to determine the perceptions of staff towards the interior space B.78 lecturer in the Department of Fine Arts Faculty of Languages and Arts, State University of Padang and identify the elements of interior space, including the situation and condition of the floor, shape the structure of the walls, ceiling design, ventilation system, lighting systems as well as the shape, layout and size of the furniture. Data was collected using observations, interviews and questionnaires. The findings of the study indicate that there is a perception of the space B.78 staff lecturer in the Department of Fine Arts Faculty of Languages and Arts, State University of Padang (1) consulting room = 6.45%, (2) meeting = 19, 35%, (3 ) workspace = 58, 06% and not at all = 16, 12%. While perceptions of lecturers towards the interior elements in space B.78 in the Department of Fine Arts Faculty of Languages and Arts, State University of Padang, which includes floor = poor (54.8%), wall = good (54.8%), good ceiling = (67.7%), ventilation system = good (58.1%), lighting system = poor (72.6%) and furniture = poor (49%).Kata kunci: persepsi, interior.